Indole-3-butyric Acid Improves Root System Quality in Guarana Cuttings - Karla Gabrielle Dutra Pinto; Sônia Maria Figueiredo Albertino; Bruna Nogueira Leite; Daniel Oscar Pereira Soares; Francisco Martins de Castro; Laís Alves da Gama; Débora Clivati; André Luiz Atroch (HortScience, 2020)
The economic potential of guarana relies on the energetic and medicinal properties of its seeds, which can be used to produce soft drinks, sticks, powder, and syrup. Brazil is the only guarana producer on a commercial scale, and the guarana crop system is the main agricultural activity in Maués, Amazonas. Although several types of technology have been developed to reduce costs and increase guarana productivity, the most important optimization of seedling production by cutting still needs to improve the rooting percentage and reduce mortality rates. However, the use of rooting inducers for guarana is still unestablished. Therefore, we evaluated the rooting potential of herbaceous cuttings from three guarana cultivars under different indole-3-butyric acid (IBA) concentrations. We recorded qualitative data from the roots of the cuttings. The IBA doses did not increase the percentage of rooted cuttings; however, they increased the root system quality of the guarana cuttings. We present this rooting method for the guarana plant as the most appropriate and least costly for small producers.